Family firms are indeed better places to work than non-family firms! Socioemotional wealth and employees' perceived organizational caring. Issue 1 (March 2021) - Christensen-Salem, Amanda; Mesquita, Luiz F.; Hashimoto, Marcos; Hom, Peter W.; Gomez-Mejia, Luis R.
Abstract: We address an ongoing controversy over whether family firms are better or worse places to work than are non-family firms. Extending socioemotional wealth theory based on the behavioral agency model, we argue that family owners strive to protect and enhance their socioemotional endowments by fostering stronger perceptions of organizational caring among their employees compared to those working for non-family firms. We develop and validate an employee perceived organizational caring (EMPOCARE) scale across three studies and test our hypotheses in a fourth study. We test a cross-level model and find that—even after controlling for formal human resource management programs and benefits—employees report higher EMPOCARE in family than non-family firms and that EMPOCARE tends to be experienced more similarly across organizational hierarchy levels in family than non-family firms. We further posit and find that EMPOCARE improves firm-level labor productivity and individual-level thriving at work. Empirical support for our cross-level EMPOCARE model comes from survey and archival data from 54, 000+ employees in 180 firms in Brazil. We discuss implications for theory and practice.